Synthesis of α,β-unsaturated esters via a chemo-enzymatic chain elongation approach by combining carboxylic acid reduction and Wittig reaction - Duan, Yitao; Yao, Peiyuan; Du, Yuncheng; Feng, Jinhui; Wu, Qiaqing; Zhu, Dunming (Beilstein Journal of Organic Chemistry, 2015)
α,β-Unsaturated esters are versatile building blocks for organic synthesis and of significant importance for industrial applications. A great variety of synthetic methods have been developed, and quite a number of them use aldehydes as precursors. Herein we report a chemo-enzymatic chain elongation approach to access α,β-unsaturated esters by combining an enzymatic carboxylic acid reduction and Wittig reaction. Recently, we have found that Mycobacterium sp. was able to reduce phenylacetic acid (1a) to 2-phenyl-1-ethanol (1c) and two sequences in the Mycobacterium sp. genome had high identity with the carboxylic acid reductase (CAR) gene from Nocardia iowensis. These two putative CAR genes were cloned, overexpressed in E. coli and one of two proteins could reduce 1a. The recombinant CAR was purified and characterized. The enzyme exhibited high activity toward a variety of aromatic and aliphatic carboxylic acids, including ibuprofen. The Mycobacterium CAR catalyzed carboxylic acid reduction to give aldehydes, followed by a Wittig reaction to afford the products α,β-unsaturated esters with extension of two carbon atoms, demonstrating a new chemo-enzymatic method for the synthesis of these important compounds.
Keywords: α,β-unsaturated esters; carboxylic acid reductase; chemoenzymatic synthesis; reduction; Wittig reaction

(untitled) - Shibata, K.; Chatani, N. (Org. Lett., 2014)

(untitled) - Cheng, J.; Huang, Z.; Chi, Y. R. (Angew. Chem., Int. Ed., 2013)

(untitled) - Wang, P.; Ling, L.; Liao, S.-H.; Zhu, J.-B.; Wang, S. R.; Li, Y.-X.; Tang, Y. (Chem. – Eur. J., 2013)

(untitled) - Hashimoto, T.; Maruoka, K. (Chem. Rev., 2015)

(untitled) - Zhu, Y.; Wang, Q.; Cornwall, R. G.; Shi, Y. (Chem. Rev., 2014)

(untitled) - He, J.; Ling, J.; Chiu, P. (Chem. Rev., 2014)

(untitled) - Yasukawa, T.; Suzuki, A.; Miyamura, H.; Nishino, K.; Kobayashi, S. (J. Am. Chem. Soc., 2015)

(untitled) - Weber, F.; Brueckner, R. (Eur. J. Org. Chem., 2015)

(untitled) - Peacock, L. R.; Chapman, R. S. L.; Sedgwick, A. C.; Mahon, M. F.; Amans, D.; Bull, S. D. (Org. Lett., 2015)

(untitled) - Niu, Z.; Chen, J.; Chen, Z.; Ma, M.; Song, C.; Ma, Y. (J. Org. Chem., 2015)

(untitled) - Parveen, S.; Hussain, S.; Qin, X.; Hao, X.; Zhu, S.; Rui, M.; Zhang, S.; Fu, F.; Ma, B.; Yu, Q.; Zhu, C. (J. Org. Chem., 2014)

(untitled) - Hatano, M.; Horibe, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Časar, Z.; Steinbücher, M.; Košmrlj, J. (J. Org. Chem., 2010)

(untitled) - Oliveira, M. E. R.; da Silva Filho, E. C.; Filho, J. M.; Ferreira, S. S.; Oliveira, A. C.; Campos, A. F. (Chem. Eng. J., 2015)

(untitled) - Nakagiri, T.; Murai, M.; Takai, K. (Org. Lett., 2015)

(untitled) - Liu, J.; Liu, Q.; Franke, R.; Jackstell, R.; Beller, M. (J. Am. Chem. Soc., 2015)

(untitled) - El-Batta, A.; Jiang, C.; Zhao, W.; Anness, R.; Cooksy, A. L.; Bergdahl, M. (J. Org. Chem., 2007)

(untitled) - Chen, Y.; Romaire, J. P.; Newhouse, T. R. (J. Am. Chem. Soc., 2015)

(untitled) - Kona, J. R.; King'ondu, C. K.; Howell, A. R.; Suib, S. L. (ChemCatChem, 2014)

(untitled) - Shearouse, W. C.; Korte, C. M.; Mack, J. (Green Chem., 2011)

(untitled) - Zeitler, K. (Org. Lett., 2006)

(untitled) - Kantam, M. L.; Kumar, K. B. S.; Balasubramanyam, V.; Venkanna, G. T.; Figueras, F. (J. Mol. Catal. A: Chem., 2010)

(untitled) - List, B.; Doehring, A.; Hechavarria Fonseca, M. T.; Job, A.; Rios Torres, R. (Tetrahedron, 2006)

(untitled) - Barma, D. K.; Kundu, A.; Bandyopadhyay, A.; Kundu, A.; Sangras, B.; Briot, A.; Mioskowski, C.; Falck, J. R. (Tetrahedron Lett., 2004)

(untitled) - Maryanoff, B. E.; Reitz, A. B. (Chem. Rev., 1989)

Reductions by the Alumino-and Borohydrides in Organic Synthesis - Seyden-Penne, J. (Wiley-VCH, 1997)

(untitled) - Napora-Wijata, K.; Strohmeier, G. A.; Winkler, M. (Biotechnol. J., 2014)

(untitled) - Duan, Y.; Yao, P.; Chen, X.; Liu, X.; Zhang, R.; Feng, J.; Wu, Q.; Zhu, D. (J. Mol. Catal. B: Enzym., 2015)

(untitled) - Venkitasubramanian, P.; Daniels, L.; Rosazza, J. P. N. (J. Biol. Chem., 2007)

(untitled) - He, A. M.; Li, T.; Daniels, L.; Fotheringham, I.; Rosazza, J. P. N. (Appl. Environ. Microbiol., 2004)

(untitled) - Li, T.; Rosazza, J. P. (J. Bacteriol., 1997)

WO Patent - Behrouzian, B.; McDaniel, R.; Zhang, X.; Clark, L. (Engineered Biosynthesis of Fatty Alcohols, 2010)

(untitled) - Akhtar, M. K.; Turner, N. J.; Jones, P. R. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Shtratnikova, V. Y.; Bragin, E. Y.; Dovbnya, D. V.; Pekov, Y. A.; Schelkunov, M. I.; Strizhov, N.; Ivashina, T. V.; Ashapkin, V. V.; Donova, M. V. (Genome Announce., 2014)

(untitled) - Li, T.; Rosazza, J. P. (J. Biol. Chem., 1998)

(untitled) - van den Ban, E. C. D.; Willemen, H. M.; Wassink, H.; Laane, C.; Haaker, H. (Enzyme Microb. Technol., 1999)